The Development of English E-Modules Based on Multicultural and Contextual Teaching Learning Approach to Improve Student Learning Outcomes - Muchammad Arosyad; Mohamad Jazeri2; Binti Maunah; Choiruddin Choiruddin (Jurnal Teknologi Pembelajaran, 2021)
The difficulties in English learning can be caused by the lack of media innovation in the learning. This study aims to develop an English e-module using a multicultural-based contextual teaching, and learning approach for grade V at elementary school, the effectiveness, and the effect of using that media. The method used the Research and Development of the Borg and Gall model that modified by Sugiyono, until the 7th step. The research objects were 42 students in grade V-A and V-B, and the data analysis showed that (1) The design of e-module development by analyzing the needs of learning media that produced in the form of an English E-Module focuses on a contextual approach, and conveys various cultures. In addition, it also provides a place to learn while playing, a colorful display to attract the interest of students to be motivated to learn English. (2) The results of product effectiveness by media experts are 99.5% from the first media expert, and 90.5% from the second media expert. The results of the subject validation analysis by the first subject expert are 93.25% and the second subject expert is 80.5% (3) Based on the data analysis of the pre-test and post-test scores with t-test analysis, it is known that the significance value is 0.00 < 0.05. The data above shows that there is a significant effect on the use of the English E-Module that has been developed to improve learning outcomes for grade V.